Pengaruh pemecahan saham terhadap harga saham dan volume perdagangan saham pada perusahaan go public di bursa efek indonesia (periode 2011-2016 - Irma Amrianti Nasir; Zainal Ilmi; Irsan Tricahyadinata (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this research is to know the difference of stock price and trading volume activity before and after the existence of stock splits in the Indonesia Stock Exchange. The price share and trading volume activity used in this research is from the companies that are doing stock splits which consist of 47 companies at five days before and five days after stock splits in the year range of time between 2011-2016 period of research. Data analysis tool uses the test of Paired Sample T-Test.The results of the research indicate that there is a significant effect on the stock price and there is no any significant effect on the trading volume activity before and after stock splits. This research also shows the difference of stock price before and after the stock splits with the result of 111.47881 with 0.002 significance. Due to the significance 0.05 (0.002 0.05), it can be interpreted that there is a significant difference of the stock price before and after stock splits. Meanwhile, for the difference of trading volume activity, the result is 503,789,7915 with 0.649 significance, due to the significance 0.05 (0.649 0.05), it can be interpreted that there is an insignificant trading volume activity before and after stock splits. Keywords: Stock Splits, Stock Price, Trading Volume Activity